Empirical Negation, Co-Negation and the Contraposition Rule II: Proof-Theoretical Investigations - Niki, Satoru (Bulletin of the Section of Logic, 2020)
We continue the investigation of the first paper where we studied logics with various negations including empirical negation and co-negation. We established how such logics can be treated uniformly with R. Sylvan's CCω as the basis. In this paper we use this result to obtain cut-free labelled sequent calculi for the logics.